Distribution and FTIR-based fingerprint of secondary metabolites in different organs of ant-plant (Myrmecodia tuberosa) - NIYA BUDHI LESTARI; YOHANA C. SULISTYANINGSIH; ABDUL HALIM UMAR; DIAH RATNADEWI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Lestari NB, Sulistyaningsih YC, Umar AH, Ratnadewi D. 2024. Distribution and FTIR-based fingerprint of secondary metabolites in different organs of ant-plant (Myrmecodia tuberosa). Biodiversitas 25: 1104-1115. Myrmecodia tuberosa Jack, or ant-plant, is widely used as a traditional medicine. The plant has the potential to be antimicrobial, anticancer, and antioxidant. Its domatium is believed to contain valuable substances, rendering people to collect the organ that devastates the whole plant. Therefore, the distribution and nature of the major substances in the leaf, petiole, and domatium must be investigated. This study aimed to determine the secondary metabolites and their accumulation sites through anatomy and histochemistry. Fourier-transform infrared (FTIR) and chemometrics supported the determination. Microscopic preparations made observations of the anatomy and secretory structures of transverse and paradermal sections. Histochemical studies were performed with specific reagents. M. tuberosa has a hypostomatic leaf blade with parasitic stomata. The main secretory structure is the idioblast. Idioblasts are scattered over various tissues, such as the epidermis, hypodermis, palisade, spongy mesophyll, and cuticle of the leaf blade, in the epidermal tissue, chlorenchyma cortex, and cuticle of petiole and the periderm, cortex, and pith of domatium. Terpenoids, phenols, lipophilic compounds, essential oils, and flavonoids were found in the leaf blade, petiole, and domatium, whereas alkaloids were present only in the petioles. FTIR demonstrated the main functional groups in the three organs are similar, while the principal component analysis distinguished domatium from leaf blade and petiole.